Evoking pyroptosis with nanomaterials for cancer immunotherapy: Current boom and novel outlook - Wen-Da Wang; Zhi-Jun Sun (Nano TransMed)
ABSTRACT: Cancer immunotherapy, including immune checkpoint blockade, has emerged as a powerful and effective clinical strategy for the treatment of tumors. However, the low response rates or systemic adverse effects owing to the heterogeneity of the tumor microenvironment limit the efficacy of cancer immunotherapy. Pyroptosis, featuring inflammation and lysis, can promote the release of large amounts of proinflammatory agents that reprogram the tumor microenvironment and is expected to achieve the transition from “cold” tumors to “hot” tumors. Therefore, understanding how to particularly evoke tumor cell pyroptosis is crucial in overcoming the adverse effects associated with the tumor microenvironment. The development of emerging nanotechnology offers an avenue for tumor-targeted drug development. Nanomaterials that can trigger tumor-specific pyroptosis have promising applications in improving the efficacy of cancer immunotherapy while reducing systemic adverse effects. Herein, we review the fundamentals of pyroptosis, and summarize the strategies of pyroptosis-based nanomaterials that have been developed recently, with emphasis on their utility and benefits in cancer immunotherapy. Furthermore, we put forth our viewpoints regarding the investigation of nanomaterials and suggest future directions for this rapidly developing field.